2020
DOI: 10.1002/ece3.5996
|View full text |Cite
|
Sign up to set email alerts
|

Tunicate bulb size variation in monocots explained by temperature and phenology

Abstract: Plant bulbs are modified shoot systems comprised of short internodes with apical bud(s) surrounded by layers of leaf bases. Bulb diameters can vary greatly, with overall bulb size playing a role in flower formation and resource allocation. Despite the importance of bulb size to the overall fitness of an individual, evolutionary and ecological aspects of this trait have been almost completely neglected. Examining over 2,500 herbarium vouchers for 115 selected species, we analyzed monocot tunicate bulb size with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 88 publications
(144 reference statements)
1
14
0
Order By: Relevance
“…Biological collections harbor an enormous wealth of data and are actively being used to investigate ecological and evolutionary processes (Soltis, 2017; Howard and Cellinese, 2020). Unfortunately, many geophytic belowground organs lack representation in herbaria (Table 1).…”
Section: Filling In the Holes Of Geophytic Researchmentioning
confidence: 99%
“…Biological collections harbor an enormous wealth of data and are actively being used to investigate ecological and evolutionary processes (Soltis, 2017; Howard and Cellinese, 2020). Unfortunately, many geophytic belowground organs lack representation in herbaria (Table 1).…”
Section: Filling In the Holes Of Geophytic Researchmentioning
confidence: 99%
“…Hysteranthy in Nervilia has been interpreted as an adaptation to marked seasonality in rainfall (Pettersson, 1991), with initiation of the generative shoot in most Nervilia species (including N. nipponica ) generally observed to coincide with the onset of early summer rains. However, Howard and Cellinese (2020) argue that hysteranthy across a broader range of bulbous plant species is more strongly correlated with occurrences in warmer, less thermally variable climates as compared to synanthous taxa, suggesting that it is more likely to be an adaptive response to temperature rather than precipitation.…”
Section: Habitatmentioning
confidence: 99%
“…If the primary function of the storage organ is to enable persistence through unfavorable periods by supplying water, carbohydrates, or both, the size of the storage organ might be expected to be correlated with the length or severity of the unfavorable season (Dafni et al, 1981; Howard and Cellinese, 2020). Consistent with this hypothesis, Fragman and Shmida (1996) reported that the bulb size of desert geophytes is larger than that of mediterranean congeners.…”
mentioning
confidence: 99%
“…The multitude of selective pressures that act on storage organ size may explain the lack of clear, discernable patterns in bulb, tuber, or corm size with length and severity of drought across multiple lineages. Storage organ size has been shown to be influenced by phylogenetic lineage (Proches et al, 2006), but considerable variation exists (Howard and Cellinese, 2020).…”
mentioning
confidence: 99%
See 1 more Smart Citation